Diseño y construcción de un molino para triturar hojas disecadas de plantas medicinales para ingrediente del té sachet, con capacidad de 25 kg/h para "La Fundación Familia Salesiana Salinas". - Pallasco Vizuete, Luis Francisco (2018)
The purpose of this project is the design and construction of a mill to crush dissected leaves of medicinal plants for tea ingredients, with a capacity of 25 kg / h for the Salesian Family Foundation Salinas. The project explains about the 12 leaves to be crushed for: medicinal uses, place of the crops, tea production process the importance handling of food is also considered to obtain the correct parameters of design and functionality of the equipment. Based on the theoretical explanation of crushing and mill alternatives, it select the most appropriate method to obtain the degree of grinding used in the mix of aromatic infusions, thus obtaining the design parameters. The analysis patterns of elements are also presented, as well as the selection of the standard elements and selection of materials, used in the construction of the mill. An analysis is made of the economic resources used for the construction of the mill and the economic results in the tests with it. Finally, conclusions and recommendations are established in this project.